Pulmonary Consequences of Prenatal Inflammatory Exposures: Clinical Perspective and Review of Basic Immunological Mechanisms - Jackson, Courtney M.; Mukherjee, Shibabrata; Wilburn, Adrienne N.; Cates, Chris; Lewkowich, Ian P.; Deshmukh, Hitesh; Zacharias, William J.; Chougnet, Claire A. (Frontiers in Immunology, 2020)
Chorioamnionitis, a potentially serious inflammatory complication of pregnancy, is associated with the development of an inflammatory milieu within the amniotic fluid surrounding the developing fetus. When chorioamnionitis occurs, the fetal lung finds itself in the unique position of being constantly exposed to the consequent inflammatory meditators and/or microbial products found in the amniotic fluid. This exposure results in significant changes to the fetal lung, such as increased leukocyte infiltration, altered cytokine and surfactant production, and diminished alveolarization. These alterations can have potentially lasting impacts on lung development and function. However, studies to date have only begun to elucidate the association between such inflammatory exposures and lifelong consequences such as lung dysfunction. In this review, we discuss the pathogenesis of and fetal immune response to chorioamnionitis, detail the consequences of chorioamnionitis exposure on the developing fetal lung, highlighting the various animal models that have contributed to our current understanding and discuss the importance of fetal exposures in regard to the development of chronic respiratory disease. Finally, we focus on the clinical, basic, and therapeutic challenges in fetal inflammatory injury to the lung, and propose next steps and future directions to improve our therapeutic understanding of this important perinatal stress.